The silver chair - Lewis, C.S. (Clive Staples) 1898-1963 (New Delhi Harper Collins, 1953)
Narnia ... where giants wreak havoc ... where evil weaves a spell ... where enchantment rules. Through dangers untold and caverns deep and dark, a noble band of friends is sent to rescue a prince held captive. But their mission to Underland brings them face-to-face with an evil more beautiful and more deadly than they ever expected. The Silver Chair is the sixth book in C.S. Lewis?s The Chronicles of Narnia, a series that has become part of the canon of classic literature, drawing readers of all ages into a magical land with unforgettable characters for over fifty years. This is a complete stand alone read, but if you want to discover what happens in the final days of Narnia, read The Last Battle, the seventh and concluding book in The Chronicles of Narnia.
Keywords: Fiction; Narnia (Imaginary place); Voyages, Imaginary; Good and evil; Voyages and travels; Fantasy fiction